Il sistema delle orchestre e dei cori giovanili di Abreu nel contesto occidentale. Un tentativo di dare significato pedagogico al trapianto dell'esperienza venezuelana - Daniele Branca (Firenze University Press, 2015)
The System of Children and Youth Choirs and Orchestras founded forty years ago by Josè Antonio Abreu in Venezuela, has become a significant alternative to the social ills faced by children and young people of the most disadvantaged neighborhoods of the South American metropolis, not only drugs and crime, but also the nihilistic logic that lacks all hope. It makes sense to transfer this experience in the wealthy West where the discomfort takes different forms? The answer is positive: music made together is ideal for sharing basic social values, construction of meaning and important experiences. The group is a perfect example of positive interdependence, commitment and responsibility, emblem of the community, micro-ideal society. Tolerance, inclusion, shared goals: values that can be a solution as well for our ills (bullying, eating disorders, depression, immaturity, inability to decision and commitment, dependence on families etc.). The System of Abreu is the credible alternative to the traditional way of teaching music, cold and elitist, and it stresses the importance of teachers in their role of great responsibility, both pedagogical and psychological.